PEMETAAN SOSIAL DAN PARTISIPASI STAKEHOLDER DALAM PERENCANAAN PROGRAM PEMBERDAYAAN MASYARAKAT - Rela, Iskandar Zainuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
Community empowerment programs that are effective, right on target, and provide solutions to community problems are programs planned based on data and information in the field and designed in a participatory manner by involving stakeholders. This research aims to discover local communities' issues and phenomena, mainly social, economic, and environmental, through social mapping studies and design community empowerment programs for sustainable development. The method used in this research is descriptive. Data collection techniques are carried out using the Rapid Rural Appraisal (RRA) method with household survey techniques, Focus group Discussions (FGDs), and semi-structured interviews. They involve three villages affected by mining activities, which are recipients of CSR funds. From the results of the analysis and discussion obtained, information that the level of stakeholder participation in the identification of issues for community empowerment is a high-level category. This is shown in their involvement in the process of FGD activities. Identified issues and community empowerment programs include agriculture, animal husbandry and fisheries, health, public infrastructure, education and human resources, social and religious areas, and youth or youth organizations. Strategic issues as a reference in implementing sustainable community empowerment programs are encouraging the improvement of the regional economy and community income, developing agriculture, livestock, and fisheries, sustainable community empowerment programs based on stakeholder recommendations, strengthening institutions and partnerships, and developing infrastructure and improving essential health services.